Tag single nucleotide polymorphisms of alcohol‐metabolizing enzymes modify the risk of upper aerodigestive tract cancers: HapMap database analysis. Issue 5 (22nd October 2012) - Chung, C.‐S.; Lee, Y.‐C.; Liou, J.‐M.; Wang, C.‐P.; Ko, J.‐Y.; Lee, J.‐M.; Wu, M.‐S.; Wang, H.‐P.
Summary Although alcohol is associated with higher upper aerodigestive tract (UADT) cancer risk, only a small fraction of alcoholics develop cancers. There is a lack of evidence proving the association of tag single nucleotide polymorphisms of alcohol‐metabolizing enzymes with cancer risk. The aim of this study was to determine the association of these genetic polymorphisms with UADT cancer risk in a Chinese population. It was a hospital‐based case–control candidate gene study. The databases of the International HapMap Project were searched for haplotype tag single nucleotide polymorphisms of the genes alcohol dehydrogenase (ADH)1B, ADH1C, and aldehyde dehydrogenase (ALDH)2. The genotyping was performed by the Sequenom MassARRAY system. Totally, 120 head and neck squamous cell carcinoma, 138 esophageal squamous cell carcinoma patients, and 276 age‐ and gender‐matched subjects were enrolled between June 2008 and June 2010.Minor alleles of ADH1B (rs1229984) and ALDH2(rs671) were not only associated with the risk of UADT cancers (odds ratio [OR] [95% confidence interval, CI]: 3.53 [2.14–5.80] and 2.59 [1.79–3.75], respectively) but also potentiated the carcinogenic effects of alcohol (OR [95% CI]: 53.44 [25.21–113.29] and 70.08 [33.65–145.95], respectively). Similar effects were observed for head/neck and esophageal cancer subgroups. Multivariate logistic regression analysis identified four significant risk factors, including habitual use of cigarettes, alcohol, betel quid, and lower body mass index (P < 0.001). The haplotypes GAGC (OR 1.61, 95% CI 1.08–2.40, P = 0.018) and CCAATG (OR 1.69, 95% CI 1.24–2.30, P < 0.001) on chromosomes 4 and 12, respectively, were associated with higher cancer risk. These findings suggested that risk allele or haplotype carriers who consume alcohol and other carcinogens should be advised to undergo endoscopy screening. The information can be used to determine the degree of susceptibility of each subject and can be combined with other environmental factors, like carcinogen consumption, in the screening analysis.